Evaluation of uncertainty in safety integrity level calculations. Issue 4 (23rd January 2016) - Freeman, Raymond "Randy"; Summers, Angela
Abstract : The evaluation of the safety integrity level (SIL) of a new or existing safety instrumented system (SIS) requires detailed calculations based on the failure rates of the device and the planned maintenance‐testing cycle for the system. The failure rates of the devices are taken from standard failure rate tabulations of equipment. The maintenance and testing plans are developed based on plant experience. The quantitative evaluation determines the probability of failure on demand (PFD) for a demand mode SIS and yields the SIL of the SIS. All of the data used in the SIL calculations are uncertain. This article explores the impact of uncertainty on the PFD calculation for a SIS. The "70%" rule of thumb from IEC 61508 is compared to results obtained using probability theory such as variance contribution analysis (VCA). A proposed methodology for handling the uncertainty in the PFD calculations is presented based on the application of the VCA method. An example is worked to demonstrate the methodology. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 341–348, 2016